THE IMPLEMENTATION OF RAMIT TECH ROBOT ACCOUNTANT TO IMPOVE THE EFFICIENCY OF BOOKKEEPING AND FINANCIAL REPORTING IN BANYUMANIK HOSPITAL - Ramdhan Rodia Muhammad; Surya Raharja (Diponegoro Journal of Accounting, 2021)
This research aims to analyze the implementation of RAMIT Tech Robot Accountant, which is a digital robot originally programmed by the author, whether it improves the efficiency of bookkeeping and financial reporting, and how the efficiency is improved. The digital robot is meant to be implemented on accounting information system of Banyumanik Hospital in Semarang, Indonesia. It has the capability of doing the bookkeeping and financial reporting by itself, including journalizing transactions, producing balance Sheet, income Statement, cash flow, and changes on equity. All of those thing can be achieved by the robot with minimum or without human intervention. The result of the research conducted would likely help the author to know whether the RAMIT Tech Robot Accountant improves the efficiency of bookkeeping and financial reporting or not and discover how the efficiency is improved. The result will help the development of the author’s digital robot in the future. The research is an action research. The steps of the research can be summarized into 4 steps, which are Planning (situational analysis), Implementation of Action (acting), Observing (acting), and Evaluation (reflecting). The author used the qualitative approach by descriptive analysis, and perform the analysis technique with PIECES Analysis, system analysis, weakness analysis and needs analysis. Data has been collected through action (intervention), interview, discussion, observation, documentation, and evaluation. The research was conducted in 1 year.The result has shown that RAMIT Tech Robot Accountant improves the efficiency of Bookkeeping and Financial Reporting in the hospital. The digital robot improves the efficiency by giving more performance with more results and less effort, eliminating cost or expense of human accountant, giving better information system management and increasing consistency and accuracy. However, the RAMIT Tech Robot Accountant in current development still has some limitation in processing the transaction data. The digital robot is only capable of processing digital data and not capable of processing analog data. Although the digital robot still has some limitation, the robot can improve the efficiency of bookkeeping and financial reporting in Banyumanik Hospital and is able to take some role of accounting staff in Banyumanik Hospital.